Joint Power and Multiple Access Control for Wireless Mesh Network with Rose Projection Method - Meiqin Tang; Lili Shang; Yalin Xin; Xiaohua Liu; Xinjiang Wei (The Scientific World Journal)
This paper investigates the utility maximization problem for the downlink of the multi-interface multichannel wireless mesh network with orthogonal frequency division multiple access. A cross-layer joint power and multiple access control algorithm are proposed. Rosen projection matrix is combined with Solodov projection techniques to build a three-memory gradient Rosen projection method, which is applied to solve this optimization problem. The convergence analysis is given and simulations show that the proposed solution achieves significant throughput compared with existing approaches.